EFFECT OF OXYGEN FUGACITY ON THE ETCHING RATE OF DIAMOND CRYSTALS IN SILICATE MELT - Sonin V.M.; Zhimulev E.I.; Fedorov I.I.; Chepurov A.I. (My University, 2006)
Experimental data on the etching of diamond crystals in basaltic melt at 1130°C with variable oxygen fugacity in the environment are considered. The oxygen fugacity was set with the HM and NNO buffers. The study was carried out on a 0.6 - 0.8 mm fraction (powder) of natural diamond crystals. It has been established that, at the same temperature, the rate of diamond etching (oxidation) in silicate melt depends on the oxygen fugacity in the environment. The etching rate decreases with decline in the oxygen fugacity from the case where the melt comes into contact with atmospheric air to the conditions controlled by the HM and NNO buffers. Under the conditions of the HM and NNO buffers, oxidation was accompanied by surface graphitization of diamond crystals. © Pleiades Publishing, Inc. 2006.